A review of stakeholder interests and participation in the sustainable use of communal wetlands: the case of the Lake Fundudzi catchment in Limpopo Province, South Africa - Silima, Vhangani (Rhodes University, Faculty of Education, Department of Education, 2007)
Many rural South African people depend on natural resources for their survival. Wetlands provide some of those natural resources. These are presently are under pressure due to high demand, overexploitation and poor land management. The history of South Africa has been characterised by exclusion of local communities in the process of decision-making and general management of natural resources. Participation of all stakeholders is crucial for successful sustainable natural resource management. Various South African departments are engaged in a number of strategies for promoting meaningful participation of local communities. The South African laws promoting protection and sustainable use of natural resources incorporate democratic principles that require high level of participation from resource users, local communities in particular. Most of the participation techniques used are focused on satisfying political mandates and do not respond to the social context of the resource users. The aim of the study was to review the participation of stakeholders in the project of promoting the sustainable use and protection of the Lake Fundudzi catchment. The idea was to probe stakeholder interests more carefully, and to research tensions that arise in the participation process, using qualitative methodologies. Through the use of questionnaires, observations and document analysis stakeholders' interests were identified to assess their influence in the process of participation of local stakeholders. The review of stakeholders' participation in the Lake Fundudzi Project showed that stakeholders' interests are crucial for meaningful local community participation, communication and education influence. They enable meaningful participation and empowerment. A multi-stakeholders approach enables stakeholders to share roles and responsibilities and the participation process offers an opportunity for local stakeholders to participate democratically in the Project. Power relations affect stakeholder participation, capital dependant participatory initiatives are likely to be at risk, participatory processes are likely to promote the empowerment and knowledge exchange amongst stakeholders, the views of local stakeholders are not always considered by outside support organisation and multi-stakeholder participatory approaches enable the initiative/activity/project to achieve its objectives.
Keywords: Wetland ecology -- South Africa -- Limpopo; Wetland management -- South Africa -- Limpopo; Natural resources -- Management -- South Africa -- Limpopo; Conservation of natural resources -- South Africa -- Limpopo; Conservation of natural resources -- Citizen participation -- South Africa -- Limpopo; Sustainable development -- South Africa -- Limpopo